Perancangan Arsitektur Enterprise Dengan Menggunakan Togaf ADM (Studi Kasus : CV. Qay Bersaudara) - Gusriyanti, Dwi Ayu (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2025)
Abstract− An important strategy in dealing with developments in information technology is the use and improvement of information system support for enterprises. CV. Qay Bersaudara is a company engaged in the wood processing industry. In carrying out organizational activities, it always leads to customer satisfaction in accordance with the vision and mission which are the goals and objectives. CV business activities. Qay Bersaudara can be identified as the main and supporting business functions. The main identification includes processing wood data, to selling wood processing waste. Meanwhile, the supporting businesses include human resource management, infrastructure management and financial management. Both business areas in their operations support each other. Analysis of the processes and functions of the main and supporting business activities of CV. Qay Bersaudara was carried out in order to understand the needs that arise from the problems in each of these activities. For architectural design includes vision architecture, business architecture, information system architecture and technology architecture at CV. Qay Bersaudara to achieve the goals of the organization, the authors use the TOGAF ADM Framework. Keywords: Design, Architecture, Enterprise, Togaf ADM